RELATIONSHIP BETWEEN PREGNANT WOMEN'S KNOWLEDGE AND ANTENATAL CARE VISITS FOR PREGNANT WOMEN IN THE WORK AREA OF POPAYATO BARAT PUBLIC HEALTH CENTER, POHUWATO DISTRICT, GORONTALO PROVINCE - Utina, Djoko Ismanto; Wulansari, Ika; Hiola, Dewi Suryaningsi; Ningtias, Ayu (Medical and Health Journal, 2025)
The Maternal Mortality Rate (MMR) in Indonesia remains one of the highest in Southeast Asia, indicating unequal access to healthcare services. Antenatal Care (ANC) visits are a crucial indicator in reducing MMR; however, ANC visits coverage in several areas, including Pohuwato Regency, Gorontalo Province, remains below the target. Thus, this research aims to identify and analyze the factors associated with ANC visits in the working area of the UPTD Puskesmas Popayato Barat, Pohuwato Regency, Gorontalo Province. This research is an analytical survey research utilizing a cross-sectional design. The population consists of all pregnant women in the working area of Puskesmas Popayato Barat, totaling 66 individuals. The sampling method is done through non-probability sampling with a purposive sampling technique, selected based on specific criteria relevant to this research. The sample size is determined using Yamane's formula, resulting in a total of 57 respondents. The analyzed variables include knowledge, family support, healthcare provider support, distance to healthcare facilities, and ANC visits. The data are collected using questionnaires and analyzed using the Chi-Square test. The findings show that there is a significant relationship between pregnant women’s knowledge (p<0.05), family support (p<0.05), and healthcare provider support (p<0.05) with ANC visits. Conversely, distance to healthcare facilities did not show a significant correlation. Transportation barriers, limited support from healthcare providers, and insufficient knowledge among pregnant women regarding the importance of ANC also influenced the low ANC visit coverage. Thus, this research concludes that increasing knowledge, enhancing family support, and strengthening the role of healthcare providers is essential to improve ANC visits, ultimately contributing to the reduction of MMR in Pohuwato Regency.